“Kotak Kosong” Bernama Paket Paralel Perizinan: Sebuah Content Analysis Kewenangan Perizinan Oleh Pemerintah Daerah Pasca Undang-Undang Cipta Kerja - Muhammad Najih Vargholy; Mohamad Rifan; Syahrul Sajidin; Liavita Rahmawati (Jurnal Risalah Hukum, 2023)
The psychological condition of forming laws and regulations that lead to investment optimization through various licensing and investment policies is an important aspect in viewing the diorama of licensing developments in Indonesia, one of which was initiated by Law Number 11 of 2020 on Job Creation. Displacement specimen decentralized to semi-centralized licensing is one of the consequences of the policy package in the Job Creation Law. This paper was written using the normative research method with 4 (four) types of approaches: statute, conceptual, comparative, and futurist. The discussion in this paper boils down to licensing rationalization at the regional level which is termed "Empty Packages'', although the regulatory framework related to licensing directs regional authorities to make licensing packages through PMPTSP and facilitated by Public Service Malls. This altruism towards the phrase "Empty Package" is due to socio-juridical problems in each region for their role in maintaining the health of regional investment at a point dilemma. In addition to the basic regulations in controlling/authorizing permits, there are several problems. The logical consequence is that the regional government does not have the authority in terms of enforcing business licenses that are factually contrary to the socio-juridical conditions of the region. So that in the future the results of this research need to be designed interregional linkages which directs licensing policies to be in line with central-regional investment needs with several limitations such as the size of urgent needs, feasibility, and major changes.